2022
DOI: 10.1177/00031348221075785
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with the Development of Colorectal Anastomotic Strictures Prior to Diverting Loop Ileostomy Reversal

Abstract: Background Anastomotic strictures represent a major source of morbidity in colorectal surgery with an incidence reported up to 30%. Despite this, the mechanism by which strictures develop remains unclear. This study aims to determine the incidence of colorectal anastomotic strictures and associated risk factors among a series of diverted patients. Materials and Methods A retrospective chart review was conducted of 142 patients over a 7-year period at a single institution after colorectal resection with anastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 19 publications
1
10
2
Order By: Relevance
“…In rectal cancer surgery, these studies are limited, yielding inconsistent results. [7][8][9]11 The results of this study corroborate findings from previous studies indicating that even though there is a correlation between stapler size and stricture in upper gastrointestinal tract, there is no correlation in lower GI. 1,3,8,9,14,15 Nagaoka et al Comparing 29-and 31-mm circular staplers revealed that stapler size was not a significant predictor of stricture development.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In rectal cancer surgery, these studies are limited, yielding inconsistent results. [7][8][9]11 The results of this study corroborate findings from previous studies indicating that even though there is a correlation between stapler size and stricture in upper gastrointestinal tract, there is no correlation in lower GI. 1,3,8,9,14,15 Nagaoka et al Comparing 29-and 31-mm circular staplers revealed that stapler size was not a significant predictor of stricture development.…”
Section: Resultssupporting
confidence: 90%
“…However, our findings do not support the conclusions of several studies examining the relationship between stapler size and anastomotic strictures in colorectal surgery. 7,11,16 The heterogeneity of the study participants in terms of the various surgical indications, surgical procedures, and approaches, as well as the absence of a universal definition for anastomotic strictures, can partially explain the discrepancy between our findings and those of the studies above.…”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations